Heterogeneous reduction of carbon dioxide by hydride-terminated silicon nanocrystals - Wei Sun; Chenxi Qian; Le He; Kulbir Kaur Ghuman; Annabelle P. Y. Wong; Jia Jia; Feysal M. Ali; Paul G. O’Brien; Laura M. Reyes; Thomas E. Wood; Amr S. Helmy; Charles A. Mims; et al. (Nature Communications, 2016)
Abstract Silicon constitutes 28% of the earth’s mass. Its high abundance, lack of toxicity and low cost coupled with its electrical and optical properties, make silicon unique among the semiconductors for converting sunlight into electricity. In the quest for semiconductors that can make chemicals and fuels from sunlight and carbon dioxide, unfortunately the best performers are invariably made from rare and expensive elements. Here we report the observation that hydride-terminated silicon nanocrystals with average diameter 3.5 nm, denoted ncSi:H, can function as a single component heterogeneous reducing agent for converting gaseous carbon dioxide selectively to carbon monoxide, at a rate of hundreds of μmol h−1 g−1. The large surface area, broadband visible to near infrared light harvesting and reducing power of SiH surface sites of ncSi:H, together play key roles in this conversion. Making use of the reducing power of nanostructured hydrides towards gaseous carbon dioxide is a conceptually distinct and commercially interesting strategy for making fuels directly from sunlight.